2003
DOI: 10.1261/rna.5129803
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of membrane RNAs

Abstract: Using fluorescence microscopy, we show that previously isolated membrane-binding RNAs coat artificial phospholipid membranes relatively uniformly, except for a frequent tendency to concentrate at bends, membrane junctions, and other unusual sites. Membrane RNAs can also be visualized as single molecules or isolated complexes by atomic force microscopy (AFM) of free RNAs on mica. Finally, RNAs can be seen within membranes by AFM of RNA-liposomes immobilized on hydrophobic mica surfaces. Monomer RNAs appear glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 22 publications
2
48
0
Order By: Relevance
“…RNA molecules readily bind phospholipid bilayers (Khvorova et al 1999;Vlassov et al 2001;Janas and Yarus 2003), probably residing within one of the two polar surface zones that comprise about half the membrane thickness (Wiener and White 1992). By selecting RNAs that chromatograph with liposomes, we have found many RNA complexes composed of ∼ 120 nucleotide monomers which bind to dioleoylphosphatidylcholine bilayers (Vlassov et al 2001).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…RNA molecules readily bind phospholipid bilayers (Khvorova et al 1999;Vlassov et al 2001;Janas and Yarus 2003), probably residing within one of the two polar surface zones that comprise about half the membrane thickness (Wiener and White 1992). By selecting RNAs that chromatograph with liposomes, we have found many RNA complexes composed of ∼ 120 nucleotide monomers which bind to dioleoylphosphatidylcholine bilayers (Vlassov et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…By selecting RNAs that chromatograph with liposomes, we have found many RNA complexes composed of ∼ 120 nucleotide monomers which bind to dioleoylphosphatidylcholine bilayers (Vlassov et al 2001). Such membrane RNAs oligomerize when free and, even more strikingly, within the membrane (Janas and Yarus 2003). RNAs we use here bind optimally as a 2:1 complex of RNA 9:RNA 10 with RNA contact via kissing loops (Vlassov et al 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, sphingomyelin (SM) binds RNA and prevents its degradation by RNAses [139,140]. Moreover, a few groups have reported that small RNAs could bind to phospholipid membranes using vesicular models [141][142][143][144]. Whether the plasma membrane SM, enriched into lipid rafts, could also bind miRNA and contribute to its export to HDLs has not been published so far.…”
Section: Mirna Transfer To Hdlsmentioning
confidence: 99%
“…Characterizing of the RNA complexes, which were composed of RNA 9 and RNA 10 sequences, revealed small internal loops with partially complementary sequences, leading to the formation of a "kissing-loop" complex. These complexes were further visualized via atomic force microscopy (AFM) and fluorescence microscopy [54].…”
Section: Aptamers That Bind Dopc Liposomesmentioning
confidence: 99%